Adsorption properties of Pb2+ on thermal-activated serpentine. Issue 18 (12th December 2019) - Cao, Chun-Yan; Yu, Bing; Wang, Ming; Zhao, Ying-Ying; Zhao, Yong-Hua
ABSTRACT: Adsorption properties of nature and thermal-activated serpentines to Pb 2+ in aqueous solution were investigated. The results showed that Freundlich isotherm and pseudo-second-order kinetics model were suitable to describe the adsorption process of Pb 2+ on serpentines. The thermodynamic parameters indicated that the adsorption process was endothermic and spontaneous. The serpentine activated at 700°C exhibited maximum adsorption capacity to Pb 2+ . Based on the XRD and XPS characterization, it could be found that the structure of serpentine did not change significantly during the adsorption process, and Pb 2+ was adsorbed on the serpentine surface as the precipitation of Pb(OH)Cl and Pb(OH)2 .